Design and Construction of a Flight Data Acquisition System Adapted to an Experimental Rocket Model - Urrego P., J. Alejandro; Monico, Luisa; Acosta, Harold; Reyes, German; Hernandez, Luis (TECCIENCIA, 2020)
This document describes the different stages of development need to design, build and characterize a flight data acquisition system for the experimental rocket USB - Rocket I. To do so, some simulated flight conditions collected from a computer program, and the manufacturing and assembly process of an integrated electronic circuit are presented. As a result, the flight data collected in a horizontal ground displacement and commercial flight test are presented with this device.